Role of Apamarga Kshara in Current Clinical Practice - Manmahendra,; Shailendra Singh,; Rekha Jatav,; P. Hemantha Kumar, (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda is Indian traditional medical system, in which herbal, mineral and animal products are used for treatment of disease. In which, Shalya Tantra is branch of Ayurveda in Astanga Ayurveda. Shalya Tantra field is deal with medical as well as surgical conditions. Sushrut Samhia is oldest and important text in field of Shalya Tantra written by Acharya Sushruta.In Shalya tantra sphere ample of treatment options available, In which Kshara Chikitsa very important part of Ayurveda medical field. Acharya Susshrut and Vabhagvat have saying, Kshara Chikitsa is best treatment compare to others Ayurveda therapy (Agnikarma and Raktamokshan) because of multiple mode of actions describe of Apamarga Kshara. Acharya Sushruta describe this property of Apamarga Kshara e.g., Chedan, Bhedan, Lekhan, Shoshan and suppress of three Doshas. In Current era lot of surgeons and clinician used of Kshara in External and internal intervention as per indication of Text. In this review article we are collect of all published data based on evidence based clinical practice. In which search strategy, include all clinical trials and case report published in below mentioned authentic search engine. All literature collects from Google Scholar, PubMed and Cochrane library. Aim of this literature review update of all researchers and clinicians regarding to Kshara Chikitsa and new development of infield Kshara Karma.